The actin filament pointed-end depolymerase Srv2/CAP depolymerizes barbed ends, displaces capping protein, and promotes formin processivity - Ekram M. Towsif; Shashank Shekhar (Proceedings of the National Academy of Sciences, 2025)
Cellular actin networks exhibit distinct assembly and disassembly dynamics, primarily driven by multicomponent reactions occurring at the two ends of actin filaments. While barbed ends are recognized as the hotspot for polymerization, depolymerization is predominantly associated with pointed ends. Consequently, mechanisms promoting barbed-end depolymerization have received relatively little attention. Here, using microfluidics-assisted three-color single-molecule imaging, we reveal that cyclase-associated protein (CAP), long known for its roles in nucleotide exchange and pointed-end depolymerization, also acts as a processive depolymerase at filament barbed ends. CAP molecules track barbed ends for several minutes, inducing depolymerization rates of up to 60 subunits per second. Importantly, CAP modulates barbed-end dynamics even under cytosol-mimicking assembly promoting conditions. We further show that CAP can colocalize with both formin and capping protein (CP) at barbed ends. CAP enhances formin processivity by 10-fold, allowing CAP–formin complexes to track fast-elongating barbed ends. In contrast, CAP destabilizes CP-bound barbed ends and accelerates dissociation of CP by fourfold. Our findings, combined with CAP’s previously reported activities, firmly establish CAP as a key regulator of cellular actin dynamics.